2020
DOI: 10.3390/molecules25153452
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Saponin Diversity of Panax ginseng

Abstract: Ginsenosides are the major bioactive constituents of Panax ginseng, which have pharmacological effects. Although there are several reviews in regards to ginsenosides, new ginsenosides have been detected continually in recent years. This review updates the ginsenoside list from P. ginseng to 170 by the end of 2019, and aims to highlight the diversity of ginsenosides in multiple dimensions, including chemical structure, tissue spatial distribution, time, and isomeride. Protopanaxadiol, protopanaxatriol and C17 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 100 publications
0
63
0
1
Order By: Relevance
“…Representative dammarane-type saponins are ginsenoside (isolated from Panax ginseng), gypenoside (from Gymnostemma pentaphyllum), bacoside (from Bacopa monnieri), and gymnemic acid (from Gymnema sylvestre), all of which have been extensively studied for their biological activities [5]. Although the naturally occurring dammarane-type saponins have been studied for a long time [102], SAR studies revealed that chemically generated synthetic saponins were mainly on ginsenoside derivatives and were still far from satisfactory [103,104]. Based on the recent progress in organic synthesis (Figure 4) [105,106], several studies showed cytotoxicity against cancer cells [58,107,108], as well as antioxidative [59], antiasthma [60] and skin-protective effects [61] of ginsenoside derivatives (Table 1).…”
Section: Dammaranementioning
confidence: 99%
“…Representative dammarane-type saponins are ginsenoside (isolated from Panax ginseng), gypenoside (from Gymnostemma pentaphyllum), bacoside (from Bacopa monnieri), and gymnemic acid (from Gymnema sylvestre), all of which have been extensively studied for their biological activities [5]. Although the naturally occurring dammarane-type saponins have been studied for a long time [102], SAR studies revealed that chemically generated synthetic saponins were mainly on ginsenoside derivatives and were still far from satisfactory [103,104]. Based on the recent progress in organic synthesis (Figure 4) [105,106], several studies showed cytotoxicity against cancer cells [58,107,108], as well as antioxidative [59], antiasthma [60] and skin-protective effects [61] of ginsenoside derivatives (Table 1).…”
Section: Dammaranementioning
confidence: 99%
“…Common types of ginsenosides are protopanaxadiol (PPD), protopanaxatriol (PPT), oleanolic acid and C17 side-chain variation type (C17SCV) sapogenins based on chemical structure [ 32 34 ]. Among them, the sugar moieties in the PPD group are mostly bound to C-3 of the dammarane-type triterpenoid saponins including ginsenosides Rb1, Rg3, Rh2, and compound K (CK).…”
Section: Ginsenosidesmentioning
confidence: 99%
“…Of them, over fifty ginsenosides were isolated from 2000 to 2019. The pharmacological effects of these metabolites still have to be determined [85]. Overall, plants are an important source of complex chemical substances.…”
Section: Metabolomics Studiesmentioning
confidence: 99%